Effect of Consumption Chocolate (Theobroma Cacao L) on Cholesterol Levels in Patients With Hypercholesterolemia (study in the UPTD Puskesmas Jatiroto) - Muzaroah Ermawati Ulkhasanah; Agung Widiastuti; Mita Agustina; Tsuluts Taufiq Hidayat; Mufarohah (Proceeding of International Conference on Science, Health, And Technology, 2021)
The prevalence of hypercholesterolemia continues to increase every year and is a risk factor for heart disease which is the cause of global death to date. The use of compounds in an effort to prevent and reduce cholesterol levels is very important, namely by using chocolate which contains flavonoid compounds as antioxidants and is able to reduce cholesterol levels in the blood. This study aims to determine the effect of chocolate consumption on blood cholesterol levels in hypercholesterolemic patients. This study is a Quasi Experiment with a Pre and Post Test Design with Control Design Group with a total of 32 respondents. The control group was given simvastatin according to a doctor's prescription, while the intervention group was added 60 grams of chocolate per day for 15 days. The results of this study indicate that consuming 60 grams of chocolate per day for 15 days accompanied by consumption of simvastatin can affect blood cholesterol levels with results (p = 0.001). Consumption of 60 grams of chocolate per day for 15 days affects the decrease in blood cholesterol levels.